Terrorism and political contention: new perspectives on North Africa and the Sahel Region - Besenyő, János; Issaev, Leonid; Korotaev, Andrej Vitalʹevič (Perspectives on Development in the Middle East and North Africa (MENA) Region, 2024)
"Against the backdrop of terrorist activity and the emergence of new conflicts in the MENA region, this book identifies factors of political contestation and analyzes organizational forms and dynamics of terrorism and conflict in North Africa and the Sahel. Written by an international selection of authors from different fields, the book covers topics such as the radicalization of terrorist organizations operating in the region, the financing of terrorism, the role of migration, the radicalization of women, the influence and motives of great powers and external factors such as France in the region, and the impact of the war in Ukraine. The book appeals to scholars and students of politics and international relations as well as African and Middle Eastern studies." --